2010
DOI: 10.1007/s11458-010-0106-8
|View full text |Cite
|
Sign up to set email alerts
|

Single-source precursor route for overcoating CdS and ZnS shells around CdSe core nanocrystals

Abstract: We reported a facile route for overcoating CdS and ZnS shells around colloidal CdSe core nanocrystals. To synthesize such double shelled core/shell nanocrystals, first, CdSe core nanocrystals were prepared in a much "greener" and cheap route, which did not involve the use of hazardous and expensive trioctylphosphine. Then, a low-cost and labor-saving route was adopted for the CdS and ZnS shell growth with the use of thermal decomposition of commercial available air stable single-source precursors cadmium dieth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…During the revision of this manuscript, one referee reminded us of a report on growth of CdSe/CdS core/shell nanocrystals using Cd(DDTC) 2 as the single precursor. 18 However, the final reaction temperature in that report was set as 200 °C, which was found to be too high to maintain a zinc-blende structure in our experiments.…”
Section: ■ Results and Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…During the revision of this manuscript, one referee reminded us of a report on growth of CdSe/CdS core/shell nanocrystals using Cd(DDTC) 2 as the single precursor. 18 However, the final reaction temperature in that report was set as 200 °C, which was found to be too high to maintain a zinc-blende structure in our experiments.…”
Section: ■ Results and Discussionmentioning
confidence: 83%
“…Results revealed that it was difficult to maintain a zinc-blende structure under the traditional reaction temperature which was typically above 200 °C (see details below). During the revision of this manuscript, one referee reminded us of a report on growth of CdSe/CdS core/shell nanocrystals using Cd(DDTC) 2 as the single precursor . However, the final reaction temperature in that report was set as 200 °C, which was found to be too high to maintain a zinc-blende structure in our experiments.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In order to further enhance the emission, we adopted a single source precursor Zn(DDTC) 2 to grow a second layer of ZnS shell. The Zn(DDTC) 2 was shown to decompose at relatively low temperatures and form ZnS shells [20,21]. Here, the use of Zn(DDTC) 2 was shown to be critical for highly luminescent InP QDs.…”
Section: Resultsmentioning
confidence: 98%